The Mothers on Respect (MOR) index: measuring quality, safety, and human rights in childbirth. (December 2017) - Vedam, Saraswathi; Stoll, Kathrin; Rubashkin, Nicholas; Martin, Kelsey; Miller-Vedam, Zoe; Hayes-Klein, Hermine; Jolicoeur, Ganga; ,
Abstract: Background: Abuse of human rights in childbirth are documented in low, middle and high resource countries. A systematic review across 34 countries by the WHO Research Group on the Treatment of Women During Childbirth concluded that there is no consensus at a global level on how disrespectful maternity care is measured. In British Columbia, a community-led participatory action research team developed a survey tool that assesses women's experiences with maternity care, including disrespect and discrimination. Methods: A cross-sectional survey was completed by women of childbearing age from diverse communities across British Columbia. Several items (31/130) assessed characteristics of their communication with care providers. We assessed the psychometric properties of two versions of a scale (7 and 14 items), among women who described experiences with a single maternity provider ( n =2514 experiences among 1672 women). We also calculated the proportion and selected characteristics of women who scored in the bottom 10th percentile (those who experienced the least respectful care). Results: To demonstrate replicability, we report psychometric results separately for three samples of women (S1 and S2) ( n =2271), (S3, n =1613). Analysis of item-to-total correlations and factor loadings indicated a single construct 14-item scale, which we named the Mothers on Respect index (MORi). Items in MORi assess the nature of respectful patient-provider interactions and their impact on a person's sense of comfort, behavior, and perceptions of racism or discrimination. The scale exhibited good internal consistency reliability. MORi- scores among these samples differed by socio-demographic profile, health status, experience with interventions and mode of birth, planned and actual place of birth, and type of provider. Conclusion: The MOR index is a reliable, patient-informed quality and safety indicator that can be applied across jurisdictions to assess the nature of provider-patient relationships, and access to person-centered maternity care. Highlights: This paper introduces the Mothers on Respect Index (MORi) that can be used to measure women's experiences of respect and self-determination when interacting with their maternity care providers. We report psychometric results separately for three samples (S1 and S2) ( n =2271), (S3, n =1613). Analysis of item-to-total correlations and factor loadings indicate a reliable uni-dimensional scale (experience of respectful maternity care) for MORi, that assesses the impact of respect on woman's sense of comfort, behavior, and perceptions of racism or discrimination. Both versions of the scale exhibited good internal consistency reliability. Women from vulnerable populations and women with medical or social risk factors during pregnancy had lower MORi scores. Women under the care of midwives had higher scores, and those who planned home births reported the most respectful care. Implementation of MORi into institutional quality assurance systems could support quality improvement at both unit and regional levels by comparing respectful treatment across birth facilities.